Human Resource Development Patterns in Sidoarjo Based on Demography and Employment: Pola Pengembangan Sumber Daya Manusia di Sidoarjo Berdasarkan Demografi dan Ketenagakerjaan - Antaresta Pradipa Widyadhana; Tri Siwi Agustina (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Human resource development is a strategic prerequisite for sustainable regional development, particularly in areas experiencing dynamic demographic change. Specific Background: Sidoarjo Regency represents an economically active region in East Java with a large productive-age population, a labor market dominated by manufacturing and services, and evolving household consumption patterns. Knowledge Gap: Existing regional studies rarely integrate demographic structure, employment characteristics, skill alignment, and economic capacity within the Workforce Development Theory framework at the local level. Aims: This study analyzes human resource development in Sidoarjo Regency through demographic conditions and employment potential using a qualitative descriptive approach. Results: The findings reveal a high labor force participation rate with dominance of senior high school graduates absorbed mainly in service and manufacturing sectors, alongside persistent open unemployment and skill mismatch, particularly among secondary and higher education graduates. Economic support is characterized by concentrated MSME credit in manufacturing and increasingly modern consumption patterns, yet accompanied by welfare disparities. Novelty: This study provides an integrated regional analysis linking labor structure, participation, competency alignment, and household economic capacity within a workforce development perspective. Implications: The results indicate the need for integrated human resource development policies that align education and training with labor market demand while addressing economic inequality to support sustainable regional workforce development. Highlights: Labor participation remains high but is accompanied by persistent open unemployment and competency mismatch. Manufacturing and service sectors dominate job absorption alongside concentrated MSME financing. Rising household consumption reflects economic growth alongside continuing welfare disparities. Keywords: Human Resource Development, Employment, Demography